DISTANCE LEARNING SYSTEM FOR STUDETS OF TARRU NAMED AFTER M. H. DULATI IN THE DISCIPLINE " PHYSICAL CULTURE» - Косырева, Ирина; Рожко, Гульчехра (SWorldJournal, 2020)
Due to the current situation, universities and colleges of the Republic of Kazakhstan have completely switched to distance learning. In this article, we are teachers of the Department of "Physical education" of Tarru named after M. H. Dulati share our bes